Unraveling the Issue of Divorce Mediation in the Gorontalo Religious Court - Adriani B. Halid (Estudiante Law Journal, 2026)
The purpose of this author is to find out How Divorce In Gorontalo Religious Court is In Mediation Of Case Settlement.  The type of writing used is the author of an Empirical Normative.  Data collection techniques are carried out using interviews, observation, and literary techniques. Then the data is analyzed descriptively or provides an overview or exposure to the subject and object of the author as the result of the author’s done. The results of this author show that the effectiveness of mediation in resolving divorce cases in the Gorontalo class IA religious court has not been fully said to be effective, due to its legal factors, law enforcement factors, facilities and facilities factors, community factors, and cultural factors. Therefore, it can be concluded that the process of implementing mediation can be said to be effective while the results of the mediation carried out have not been effective. Then the factors that cause the many failures of mediation carried out by the Gorontalo Religious Court, namely factors in divorce cases, factors from litigants, factors from mediators, factors where mediation is carried out, and environmental factors.